Kolaborasi Penulis Pada Media Pustakawan Periode 2017-2019 - Rochani Nani Rahayu (Ikatan Pustakawan Indonesia, 2020)
ABSTRACT Media Pustakawan period 2017 - 2019 were analyzed using bibliometric methods aimed at finding out the number of articles, author productivity, authorship patterns, degrees of collaboration, institutions where author work, degree of collaboration , types of maritime, profession and cities where authors work. The data is downloaded from the Media Pustakawan website, https://ejournal.perpusnas.go.id/mp/index, then the data is processed using Microsof Exel and the results are presented in a table. Based on the results and discussion it can be concluded that during the period 2017 - 2019, Media Pustakawan published 96 articles, with an average productivity of 1.36 authors / articles, a single author dominated with an average degree of collaboration value of 0.271. Universities is the highest institution in contributing articles, especially from the State Islamic University. Arif Wicaksoo is the most prolific author with 4 articles, female authors are more productive than male authors. The librarian profession is in the first position as a contributor to writing, and Jakarta is the place where most authors work.